Editorial - Advancing African Women in Academia: Charting Modern Solutions - Grace Temiloluwa Agbede; Nereshnee Govender; Daisy Pillay (African Journal of Inter-Multidisciplinary Studies)
There is a gross underrepresentation of women in teaching, research, and leadership in higher education institutions (HEIs) globally. Despite the fact that a few studies have reported some gains in gender balance in HEIs, there are still glaring inequities of women in higher education, particularly in Africa. These challenges include but are not limited to, barriers to academic progression and career development, intersections of race, gender and motherhood, and identity and belonging. While several authors have revealed these gender gaps, it is valuable to understand the lived experiences of woman in academia on the African continent. African women encounter multifaceted challenges in academia. Structural barriers such as limited access to education, gender bias, and cultural norms that prioritise domestic responsibilities over career pursuits hinder their advancement (Founou et al., 2023). Additionally, the scarcity of female role models and mentors exacerbates feelings of isolation and imposter syndrome, further deterring women from pursuing academic careers. These challenges contribute to the underrepresentation of African women in leadership positions and fields traditionally dominated by men.